2019
DOI: 10.1038/s41598-019-40668-6
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes according to additional treatments after endoscopic resection for rectal small neuroendocrine tumors

Abstract: The present study aimed to investigate treatment strategies determining additional treatment after endoscopic resection (ER) of rectal neuroendocrine tumor (NET)s and long-term outcomes of endoscopically resected rectal NETs. We analyzed a total of 322 patients medical records of patients who underwent ER for rectal NETs. Rectal NETs initially resected as polyps and treated with conventional endoscopic mucosal resection (EMR) were observed more frequently in the non-curative group (P = 0.041 and P = 0.012, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 22 publications
3
23
0
Order By: Relevance
“…However, endoscopic resections have yet to prove their effectiveness (R0 resection) and safety; previous reports concerning the management of small r-NETs remain limited to several single-institution retrospective studies with a small number of cases, and large Asian studies where the epidemiology of r-NETs, endoscopic expertise and health services are different to those of Western countries. [4][5][6][7][8][9][10][11] We therefore conducted a large multicentre nationwide study in France to evaluate the outcomes of non-metastatic r-NETs 2 cm in size diagnosed endoscopically. The primary objective was to describe the proportion of R0 resection.…”
Section: Introductionmentioning
confidence: 99%
“…However, endoscopic resections have yet to prove their effectiveness (R0 resection) and safety; previous reports concerning the management of small r-NETs remain limited to several single-institution retrospective studies with a small number of cases, and large Asian studies where the epidemiology of r-NETs, endoscopic expertise and health services are different to those of Western countries. [4][5][6][7][8][9][10][11] We therefore conducted a large multicentre nationwide study in France to evaluate the outcomes of non-metastatic r-NETs 2 cm in size diagnosed endoscopically. The primary objective was to describe the proportion of R0 resection.…”
Section: Introductionmentioning
confidence: 99%
“…The key issue in the initial management of these lesions is to suspect rectal NEN based on macroscopic features before mistakenly performing routine snare polypectomy. A retrospective analysis by Lee et al [11] showed that it was possible to suspect a NET by macroscopic appearance, on endoscopy, in 95.9% of cases (94/98 lesions) [12]. These tumours are also described as hard and movable, and some authors suggested checking these features with a biopsy forceps as a helpful diagnostic tool [12].…”
Section: Clinical and Endoscopic Characteristics Of Rectal Neuroendocmentioning
confidence: 99%
“…However, the evidence supporting this management is not very strong due to the lack of large comparative studies comparing the outcomes of patients after non-curative endoscopic resection who did not undergo adjunct therapy and those who underwent salvage treatment. Cha et al followed up a group of 322 patients who underwent endoscopic resection of rNENs and found that only 31% (44/142) of the patients who did not fulfil the criteria of R0 resection underwent salvage therapy [11]. Eleven of these patients underwent surgery, and lymph node metastases were found in six patients, while there were no features of disease progression in the remaining patients [11].…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations